Inbreeding, reproductive performance, and genetic diversity in a tropically adapted dairy breed: the endangered Criollo Limonero cattle - Cartuche-Macas, Luis F.; Pérez-González, José R.; Gutiérrez-Reinoso, Miguel A.; Leal-González, Anixon G.; García-Herreros, Manuel (Frontiers in Animal Science, 2025)
Criollo Limonero cattle (Bos taurus) is an endangered bovine breed reared under the dry tropical areas of Venezuela. So far, the inbreeding and genetic diversity values of the Criollo Limonero cattle have not been assessed after more than five centuries of environmental adaptation. The main aim of the present research was to carry out a detailed analysis of the demographic status, reproductive performance, inbreeding and genetic diversity of the endangered Criollo Limonero dairy cattle using official genealogical information. Six populations were considered: historical population (individuals born between 1969–2023), and five populations born from 1974 to 2023 taken at 10-year intervals (1974–1983; 1984–1993; 1994–2003; 2004–2013; 2014–2023). Population structure variables analysed were: pedigree completeness index (PCI), number of equivalent (GEqu), complete (GCom) and maximum (GMax) generations and generation interval (GI). DG variables were: inbreeding (F), inbreeding increment (ΔF), average relatedness (AR), co-ancestry (C), Non-random mating (α), effective population size (Ne) and genetic conservation index (GCI). The gene origin probability variables were: number of founders (f), effective number of founders (fe) and ancestors (fa), number of equivalent genomes (fg), fe/fa and fg/fa ratio and DG losses. The databases were analysed by ENDOG, POPREP, and CFC software. The results indicate that the Criollo Limonero dairy breed has suffered an accelerated genetic diversity loss mainly due to the bottleneck effect and genetic drift. The average number of offspring of both males and females decreased drastically during the last period. Gmax, Gcom and GEqu showed 11.70, 2.15 and 4.58 values, respectively. Moreover, F = 4.45%, AR = 3.10%, ΔF = 0.38%, C = 1.55%, α = 0.0051, GCI = 10.35 values were obtained. Ne values showed that there is a moderate-high risk of increased inbreeding, suggesting that the population could be genetically sustainable in the medium to long term if appropriate selection and breeding schemes are carried out. In conclusion, preventing genetic diversity loss and avoiding high inbreeding values should be a priority in order to conserve the endangered Criollo Limonero dairy cattle.